2020
DOI: 10.1371/journal.pone.0239474
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning algorithm to increase COVID-19 inpatient diagnostic capacity

Abstract: Worldwide, testing capacity for SARS-CoV-2 is limited and bottlenecks in the scale up of polymerase chain reaction (PCR-based testing exist. Our aim was to develop and evaluate a machine learning algorithm to diagnose COVID-19 in the inpatient setting. The algorithm was based on basic demographic and laboratory features to serve as a screening tool at hospitals where testing is scarce or unavailable. We used retrospectively collected data from the UCLA Health System in Los Angeles, California. We included all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 15 publications
2
53
0
Order By: Relevance
“…However, few studies used laboratory, clinical, and imaging data together for COVID-19 diagnosis. Our results are in line with studies that used machine learning models based on clinico-biological variables for COVID-19 diagnosis 55 57 . The performances of these models were low, excepted for the model described by Plante and al.…”
Section: Discussionsupporting
confidence: 91%
“…However, few studies used laboratory, clinical, and imaging data together for COVID-19 diagnosis. Our results are in line with studies that used machine learning models based on clinico-biological variables for COVID-19 diagnosis 55 57 . The performances of these models were low, excepted for the model described by Plante and al.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, an algorithm based on laboratory and demographic features was proposed by Goodman-Meza D. et al [ 48 ] to serve as a screening method in hospitals where testing is limited or inaccessible. The methodology used data obtained retrospectively from the UCLA Health System in Los Angeles, California.…”
Section: Related Workmentioning
confidence: 99%
“…We evaluate and compare our proposed approach of lifelong learning and assessment against standard ML approaches on a large-scale data set. This data set comprises 127,115 samples after pre-processing and merging, which exceeds the data set size of many small scale studies [18][19][20][21][22]32 by far. Our data set comprises pre-pandemic negative samples and pandemic negative and positive samples spanning over multiple different departments of the Kepler University Hospital, Linz.…”
Section: Degrading Of Predictive Performance Over Timementioning
confidence: 99%
“…COVID-19 and the patient's prognosis can be predicted from chest CT-scans, X-rays [11][12][13][14] or sound recordings of coughs or breathing [15][16][17] . Furthermore, it has been shown that ML models based on blood tests are capable of detecting COVID-19 infection [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and predicting other outcomes, such as survival or admission to an intensive care unit [33][34][35][36][37][38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation